Significance of exercise induced ST segment elevation in patients with previous myocardial infarction. Issue 1 (January 1983) - Fox, K M; Jonathan, A; Selwyn, A
Abstract : In order to determine the significance of exercise induced ST segment elevation in patients with previous myocardial infarction, we have studied 156 patients, 26 months (mean) after myocardial infarction. Each patient underwent 16 lead precordial electrocardiographic mapping before, during, and after exercise and in addition coronary arteriography was performed. There was no significant difference in the extent of coronary disease or abnormalities of left ventricular function between patients with exercise induced ST segment elevation that was noted to occur in leads with Q waves and those with ST segment elevation plus depression or those with ST segment depression alone. Patients without exercise induced ST segment changes had fewer coronary arteries involved than those who developed ST segment changes. Nineteen patients with exercise induced ST segment elevation alone underwent coronary artery bypass surgery; in 11 this resulted in complete abolition of the exercise induced ST segment elevation and was associated with symptomatic relief and patent grafts without alteration of left ventricular function. Thus, exercise induced ST segment elevation in patients with previous myocardial infarction should be considered as important as ST segment depression in terms of underlying myocardial ischaemia, coronary anatomy, and left ventricular function.